The Iban of Sarawak, Malaysia: Ethnic Language Losing Ground to English and Sarawak Malay - Lilly, Metom; Ting, Su Hie; LING, Hsin-Nie (Human Behavior, Development and Society, 2021)
Abstract Language use by the Iban people in Sarawak, Malaysia, was studied and the focus was on the following specific objectives: (a) to describe the language use patterns of the Iban people in Iban dominant and non-Iban dominant areas in nine domains and (b) to identify the stable domains of language use for the Iban language. The data were from 84 Iban respondents, elicited using a questionnaire designed based on the UNESCO framework. The percentage of Iban usage was higher in Iban-dominant areas (30%–70%) than in non-Iban dominant areas (10%–60%). The results revealed that there was intergenerational language transmission but English was encroaching into family communications involving spouse and children. Furthermore, the usage of Iban was dwindling outside the family domain. In particular, Iban was losing ground to English in four domains (friends, classmates, workmates, and prayers) and to Sarawak Malay in two domains (public places, and market). In non-Iban dominant areas, the results on languages used in public places and in new domains (social media communication) indicate that domains of language use currently occupied by Iban may be taken over by English and Malay in the future with more ethnically-mixed family, friendship, work, and public spaces.